Noise Analysis in Urban Areas and Alternative Solutions - Baydere, Seda; Özdemir, Semahat; Özdemir, Semahat (Izmir Institute of Technology, 2000)
Nowadays, together with growing urbanisation pertaining to the numerous developments in transportation technology and also the increase in usage of new, massive and powerful machines every field, noise has become an unavoidable by-product of our mechanised life and brought about serious hazards in our health. Noise damages people's hearing mechanism and perception; harms physiological and psychological balance; decreases performance In one's works and, all in all, it spoils the peaceful atmosphere of environment. It is impossible to avoid those mentioned effects since people are likely to encounter noise everywhere. Noise can be controlled with city planning and urban design before it starts, which reduce its harmful effects on people. Yet, noise control studies in general have been conducted to reduce the noises, which are outcome of contemporary machines. Consequently, noise control studies are not adequate to inform us about what the solutions to the community notses that exist in urban areas are.This study aims at finding out what the sources of noise are in terms of community problem and determining how it affects people. What is more, this study seeks the noise control methods which have been re-established by means of planning and which are applied in the physical space in order to reduce noise. Finally in the last of this thesis, noise pollution analysis has been made in Izmir Mustafa Kemal Sahil Boulevard, as there is formerly builtup area, the noise control methods in terms of planning have been determined in accordance with the results of the noise analysis.
Thesis (Master)--Izmir Institute of Technology, City and Regional Planning, Izmir, 2000
Includes bibliographical references (leaves: 195-199)
Text in English; Abstract: Turkish and English
xvii, 229 leaves
Keywords: TD893.5.T9 B39 2000; City noise--Turkey; Noise control--Measurement; Noise pollution; Noise control--Research; City planning--Turkey